Upaya Meningkatkan Hasil Belajar Driblling Pada Permainan Sepak Bola Melalui Penerapan Model Pembelajaran Team Games Tournament Pada Siswa Kelas Vii SMP Swasta Madani - Aprilman S. Halawa; Ignasius Ivan Kurnia Ndruru; Joko Priono (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
This study aims to improve the learning outcomes of basic soccer dribbling techniques among 7th-grade students at SMP Swasta Madani through the implementation of the Team Games Tournament (TGT) learning model. The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, comprising four stages: planning, action implementation, observation, and reflection. The research was conducted over two cycles with 34 7th-grade students as subjects. Data collection techniques included observation, dribbling skill tests, documentation, and field notes. Data were analyzed using quantitative and qualitative descriptive analysis techniques. The results indicate that the implementation of the TGT learning model significantly improved students' dribbling learning outcomes. At the initial stage (pre-cycle), the average learning score was 66.25, with a classical mastery rate of 37.50%. Following the intervention in Cycle I, the average score rose to 76.81, with a classical mastery rate of 71.88%. In Cycle II, the average score increased further to 86.56, and classical mastery reached 90.63%, thereby surpassing the established success indicator—specifically, that at least 85% of students achieve a score above the Minimum Mastery Criterion (KKM) of 75. Additionally, students' learning activity, motivation, cooperation, and participation improved across each cycle. It can be concluded that the TGT learning model is effective in enhancing basic soccer dribbling skills among 7th-grade students at SMP Swasta Madani. This model fosters a learning environment that is active, collaborative, healthily competitive, and enjoyable, making it a suitable alternative for Physical Education, Sports, and Health instruction, particularly regarding basic soccer techniques.